Canadian labour market dynamics during COVID-19 - Stephen R. G. Jones; Fabian Lange; William Craig Riddell; Casey Warman (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2021)
The Canadian labour market experienced a period of unprecedented turmoil following the onset of the COVID-19 pandemic. We analyze the main changes using standard labour force statistics and new data on job postings. Envisaging a phase of temporary severing of employment relationships followed by a phase of more standard labour market search and matching, we use stock and flow data to understand key developments. We find dramatic changes in employment, unemployment and labour market attachment in 2020 and, looking forward to 2021, signs of an unusual recovery with co-existing strong labour demand and stubborn persistence in depressed employment rates.
Keywords: E24; J21; J31; 330; COVID-19; Coronavirus; Job loss; Unemployment; Employment; Transition rates